Classical philosophical and poetic thought of China and the fundamental ontology of Martin Heidegger: comparative analysis - Lu Jign (Journal of the Belarusian State University. Philosophy and Psychology, 2022)
The deep commonality of the basic concepts of Chinese classical philosophy and Heidegger’s thinking system is analysed. The relevance of identification this commonality is dictated by the powerful humanistic message of both philosophical discourses, as well as their fundamental emphasis on the practical significance, application of philosophical knowledge in everyday experience. Through the prism of the comparison undertaken, it becomes obvious that Confucianism and Taoism in China are not two parallel branches of philosophising, as they are traditionally differentiated, but different ways of talking about the same thing: ways of possibly more harmonious coexistence of the world (society, nature) and man. The mutually permeable model «M. Heidegger and Chinese philosophy», spelled out in detail, but compactly, while possibly in a more universal language, can serve as an effective methodological component of the development of research «China and the West» in the broadest sense – in other words, it can be applicable not only in philosophical, but also at the philological, cultural, social, psychological levels (or at the interdisciplinary level as a whole). In this case, we form the basic outline of the methodology of comparative study of Chinese and European (Western) poetry. The mode of human existence presented in comparison in the Chinese tradition and in M. Heidegger should then be supplemented by a comparative cross-section of the phenomenon of time – the embodiment of being for these thought systems (immediate perspective of study).
Keywords: M. Heidegger; fundamental ontology; Confucianism; Taoism; Chinese classical poetry; harmony of being